Enhancing Listening Skills in Children Aged 5-6 Years through the Use Of Spotify as a Learning Medium - Putri Nur Vita Sari; Upik Elok Endang Rasmani (Universitas Sebelas Maret, 2026)
Listening is an important skill in early childhood language development, but many children aged 5-6 years still experience obstacles. This study aims to improve listening skills through Spotify media that provides audio stories with clear sound, expressive intonation, and interesting sound effects. The study was conducted using a Classroom Action Research (CAR) approach in two cycles, each including planning, implementation, observation, and reflection. Data were collected through observation, interviews, oral/performance tests, and documentation, then analyzed qualitatively using the Miles & Huberman model (data reduction, presentation, and conclusions) and quantitatively through a comparison of the proportion of results in each cycle. The results showed an increase in children's listening skills from 26.66% in the pre-action to 46.66% in the first cycle, and reaching 80% in the second cycle. Thus, Spotify is proven to be effective as an innovative and enjoyable learning medium to support early childhood language development, especially in the listening aspect.